Restrições e dimensões dos custos de transação nos processos licitatórios na modalidade pregão eletrônico: um estudo de caso no Hospital Geral de Santa Maria - Ferrando, Magnus D' Olanda (2020)
The theme of the present study is related to the constraints of the internal phase and the dimensions of transaction costs that do interface with the transaction environment: the asset specificity, the uncertainty and the frequency, inherent to the process of execution of the e-procurement for the acquisition of medicines from the HGeSM, in the years of 2017 and 2018. The main objective is to explain the interaction of constraints and dimensions of the transaction costs in the end of the bidding processes of the e-procurement for the acquisition of medicines. The procedures used in the research, characterize it as a case study, from the point of view of its objectives, an exploratory research with a qualitative approach where were applied semi-structured interviews with executors agents and managers as well as the observation method of the involved sectors, in addition to the survey, through of the documental research, of records of the process of e-procurement processes to generate informational content with contextual value. For identification the constraints adopted Thinking Process the Theory of Constraints which was used in conjunction dimensions the Transaction Costs Theory. So, it was concluded that the lack of qualification and the accumulation of functions are the constraints of the internal phase that generate uncertainties in the forecasting of items and their quantities, which added to the specificity of the external environment for regulating drug prices are not minimized by the improvement by specialization despite the frequency in the execution of bidding processes. Soon, the management of these bidding processes of e-procurement demands special attention with specificities that must be differentiated by the agents involved, such as consumption control, process completion period and type of medication, in order to reduce the identified constraints, minimize the influence of the dimensions of the transaction costs analyzed and, consequently, reduce costs of the process.